Axial and transverse compression behaviour of Basalt fibre reinforced epoxy composite with aluminium hollow shaft with winding at different angle - Norazirahuda, Ismail (Universiti Malaysia Perlis (UniMAP), 2021)
Access is limited to UniMAP community.